Survival of mushrooms and termites upon pesticide exposure in the cocoa agro-ecosystem: Post pesticide survival of mushrooms and termites in cocoa - Eric Asare Kumi; Silas Wintuma Avicor; Yahaya Bukari; Ishmael Amoako-Attah; Solomon Agyare; Mabel Yeboah; Michael Wiafe-Kwagyan (Journal of Tropical Life Science, 2023)
Pesticides have become integral parts of cocoa cultivation for the management of insect pests and fungal pathogens which cause significant damage to the crop. However, continuous pesticides usage in the cocoa agro-ecosystem is of concern due to perceived adverse effects on non-target organisms. In this study, mushrooms and associated termites were used to elucidate the possible effect of insecticides and fungicides on non-target organisms in the cocoa agro-ecosystem.  Vegetative phase of Pleurotus sajor-caju (Oyster mushroom), Volvariella volvacea (Paddy straw mushroom), Termitomyces globulus and Termitomyces robustus (Termite mushrooms) were subjected to concentrations of commercially formulated fungicides (metalaxyl 12 % + copper (I) oxide 60 % and cupric hydroxide 77 %) and insecticides (imidacloprid 20 % and bifenthrin 2.7 %) to observe their growth rates on Potato Dextrose Agar (PDA) medium. Worker termites, Macrotermes bellicosus, were also exposed to the pesticides in Petri dishes for 24 h to observe their mortality. The manufacturer’s recommended concentration of 245 ppm for bifenthrin completely inhibited mycelial growth of all the mushrooms and caused 100% mortality of termites. At 0.0245 ppm, the insecticide caused 60% mortality of termites, but it had no inhibitory effect on the mushrooms. Except P. sajor-caju, mycelial growth of all the other mushrooms were completely inhibited by metalaxyl + copper (I) oxide at the manufacturer’s recommended concentration of 2400 ppm. However, mycelial growth rate of the mushrooms at 0.24 ppm of the fungicide was similar to the control plates. This suggests that mushrooms could survive in the cocoa agro-ecosystem amidst pesticides at lower concentrations in cocoa soils.